Diagnostic method for malignant pleural effusion distinguishing malignant mesothelioma from lung cancer using pleural carcinoembryonic antigen and hyaluronic acid levels. Issue 1 (7th January 2022) - Saraya, Takeshi; Ohkuma, Kosuke; Fujiwara, Masachika; Ishii, Haruyuki
Abstract : Abstract: Malignant mesothelioma (MM) is difficult to diagnose because of the lack of parenchymal opacities, often revealing minimal or absent pleural thickening. Furthermore, pleural effusion has diverse differential diagnoses, including malignancies, infections, as well as collagen vascular and other benign diseases. In general practice, lung cancer (LC) is the most common malignancy causing pleural effusion; therefore, a simple method using pleural diagnostic markers to differentiate between LC and mesothelioma is crucial. We retrospectively reviewed the data of 530 adult patients diagnosed with pleural effusion between January 2010 and December 2020 in an outpatient or inpatient setting. Patients with pathologically diagnosed MM or LC with cytologically positive (class IV or V) pleural effusion were analyzed, and the characteristics of these 2 diseases were compared. During the study period, 27 patients diagnosed with MM and 100 patients diagnosed with LC were enrolled. Receiver operating characteristic curve analysis demonstrated that pleural carcinoembryonic antigen (CEA) and hyaluronic acid (HA) could discriminate MM from LC with an area under the curve of 0.925 (95% confidence interval [CI]: 0.879–0.972, P  < .001) and 0.815 (95% CI: 0.686–0.943, P  < .001), respectively. To diagnose MM, the accuracy of pleural HA >30, 000 ng/mL revealed a sensitivity of 75.0%, specificity of 72.6%, and odds ratio of 7.94 (95% CI: 2.5–25.2, P  = .001); pleural CEA <6.0 ng/mL revealed a sensitivity of 95.2%, specificity of 84.9%, smaller negative likelihood ratio of 0.06, and odds ratio of 112.5% (95% CI: 14.4–878.1, P  < .001). Multiple logistic regression analysis revealed that these 2 parameters could discriminate MM from LC, with a hazard ratio of 23.6 (95% CI: 2.437–228.1, P  = .006) and 252.3 (95% Cl: 16.4–3888.1, P  < .001), respectively, and their combination had a high specificity of 98.3%. Pleural CEA (≥6.0 ng/mL) can rule out MM with a high degree of certainty, and the positive results for combination of pleural CEA <6.0 ng/mL and HA >30, 000 ng/mL can confirm MM with high specificity, prior to cytological or pathological examinations.